An Analysis of Majāzi and Haqīqi Meanings in Ilmu Dilālah: A Literature Study on Arabic Scholarly Texts - saepudin, asep; Muizzudin, Moh; Nurhamim, Nurhamim (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This article aims to examine the meaning of majāzi and hakīqi in the context of dilālah science, focusing on Arabic scholarly texts. Majāzi and hakīqi are two important terms in Arabic linguistics that refer to two types of word meanings. Majāzi is often interpreted as a figurative meaning, while hakīqi refers to the literal meaning. A deep understanding of these two concepts is essential in the analysis of scholarly texts, especially in understanding the nuances of the Arabic language which is rich in symbolism and metaphor. In this study, the author analyzes various Arabic scholarly texts that discuss majāzi and hakīqi. Through a qualitative approach, the study explores how these two meanings are used in different contexts and how they contribute to the understanding of the text. The data used in this study includes text analysis, interviews with Arabic linguists, as well as a survey of related literature. The results show that the use of majāzi and hakīqi is not only limited to linguistic aspects, but also includes cultural and philosophical dimensions. For example, in many texts, majāzi is used to convey complex ideas that cannot be explained by hakīqi meanings. Through this research, it is hoped to contribute to the development of dilālah science and enrich the understanding of the diversity of meanings in Arabic. As such, this article is not only relevant for academics, but also for practitioners working with Arabic texts in a broader context.